Editorial - Gurzynski-Weiss, Laura (Studies in Second Language Learning and Teaching, 2020)
The goal of the special issue is to provide robust examples of how we as a field can research the dynamic nature of learner individual differences (IDs). The papers in this volume provide both a sound theoretical discussion of several IDs in relationship to their (posited or empirically attested) role(s) in L2 learning, as well as specific methodological ideas on how to best reveal the dynamic nature of IDs.